HUBUNGAN KEBIASAAN MENGKONSUMSI MAKANAN DAN MINUMAN BERKARBONAT DAN BERKAFEEIN DENGAN KEPADATAN TULANG REMAJA (STUDI DI SMAN 3 SEMARANG) - Wulandari Meikawati (Jurnal Kesehatan Masyarakat Indonesia, 2008)
BACKGROAND: Calcium reqquirement during adolescence is higher than the other period of life.Caffeinated ond carbonited dink are one ofseveral factors that influence calcium icretionfrom urine.OBJECTIWS: Tofind out correlation between cffiinated and carbonated drinkconsumptionwith adolescents, bone density.MEIWOD: The method of this study wcts survey with a cross sectional approach. The population of study were of S!{AN i Semarang student in grade l" and 4 ,rt!r, subjects *"r" 7}*n througi i ,i^pt" iandon' sampling.Characteistics data, cafeinated and carbonated drink corysumption collected by qistionnati and bone ariity iy densitometry. Data analzed Pearson Product Moment and Ronk spearman Tests.RESULTS; Most of the subjects wer.e girls, aged I5 - 17 years old. Consunption of caffeinated and gqbonated dink were still within the save limit (<150 m9/dsy). As many as 18,8.% subjects had low-bofr density. However, there is no correl&ion between cottsumption of cffeinated and carbonitted drink and bone density.CONCLUSION:- There is no correlation between gonsumption if cffeinated and carbonated drink and bone density.SUGGESTION: Adolescents need higher intake of nutrientdndphysical activity to imprwg their bone densityKEY WORDS : Ado la cent, b on e de ns ity